The Relationship Between Individual Characteristics, Quality of Confinement and Recidivism by Offenders Released From Privately and Publicly Managed Residential Community Corrections Facilities - Alladin, Terrence (The prison journal, 2018)
This study examines Commonwealth of Pennsylvania state prison data on inmates released to a term of residential community corrections in either a publicly or privately managed institution (n = 7,204). Analyses indicate significant associations of race, facility orderliness, extent of educational/vocational programming, and type of facility management (Commonwealth or a private provider) with an offender’s subsequent reincarceration. Results demonstrate that private entity cost efficiency and effectiveness claims are not supported, and the growth of the private sector in Pennsylvania residential community corrections may even be having a detrimental effect on desistence efforts.